50=3x-12x+1

Simple and best practice solution for 50=3x-12x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 50=3x-12x+1 equation:


Simplifying
50 = 3x + -12x + 1

Reorder the terms:
50 = 1 + 3x + -12x

Combine like terms: 3x + -12x = -9x
50 = 1 + -9x

Solving
50 = 1 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
50 + 9x = 1 + -9x + 9x

Combine like terms: -9x + 9x = 0
50 + 9x = 1 + 0
50 + 9x = 1

Add '-50' to each side of the equation.
50 + -50 + 9x = 1 + -50

Combine like terms: 50 + -50 = 0
0 + 9x = 1 + -50
9x = 1 + -50

Combine like terms: 1 + -50 = -49
9x = -49

Divide each side by '9'.
x = -5.444444444

Simplifying
x = -5.444444444

See similar equations:

| 10x^2+3x+9=13 | | X^2-6x-11=-4 | | x*6+86=x*10-6 | | f(x)=9xsquared+5x+1 | | 2[x+8]=-4[5x-2]+8x | | 2x-7+4x+15=56 | | (4x-7)+(-12-8x)= | | 3+25x=20x+12 | | 15-4t=4 | | 3+25x=20x-12 | | e^4x=10 | | 2z(z)+20z=0 | | 3+25x=2-0x+12 | | 34+(25x)+(35x)=93 | | 34+(25x)+(35x)=94 | | (1+i)*z*z+2iz-1=0 | | 34+(25x)+(35x)=90 | | 34(25x)(35x)=90 | | 2z+20z=o | | 55-3x=6-10x | | 4x+15=-5x-12 | | 2x-5+57=3x+9 | | 5y+6-9y= | | 9x+17=4x+42 | | 13=4x-15 | | -6+(-1-b)=19 | | m^2+3=4 | | A=-3a-16 | | 3r^2=-45 | | cos(c)+3*sin(c)=2 | | x=22y+39x | | 4x-5=6x+23 |

Equations solver categories